ANALYSIS OF LEARNING MEDIA USED IN ARABIC LANGUAGE SUBJECTS IN MADRASAH - Zahro, Fatimatuz (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
The aim of this research is to determine the various uses of Arabic language learning media at the Madrasah Ibtida'iyah level which will later influence the 4 competencies that students must achieve, namely listening (istima'), speaking (kalam), reading (qiro'ah) skills. and writing (kitabah). The methodology used by the author in this research is a qualitative approach with data collection methods through interviews and observation. The results of this research show that; 1). The Arabic language learning media owned by Madrasah Ibtida'iyah Raudlatul Hasaniyah include: picture vocabulary cards, spinning wheels, styrofoam puzzles, smart snakes and ladders media, smart dice, and Arabic songs. 2). The use of Arabic learning media at MI Raudlatul Hasaniyah varies greatly, such as: adjusting learning objectives, teaching materials, learning methods used, and the use of learning media varies according to students' needs and conditions, thus influencing student understanding which can increase student motivation, reduce Student boredom also improves student memory and increases student creativity in learning.